Pelatihan Pembuatan Moringa Latte Sebagai Upaya Pencegahan Anemia di Kalurahan Ngargosari, Kulon Progo, Yogyakarta - Nur'Aini Purnamaningsih; Suwarno; Retnosyari Septiyani (CV. CENDIKIA JENIUS INDONESIA, 2024)
One of the plants often found in Ngargosari Village is the moringa plant. This community service program aims to improve community skills in innovating the manufacture of food products to prevent anemia in the form of moringa latte. This community service program aims to improve community skills in innovating the manufacture of food products to prevent anemia in the form of moringa latte. The implementation of community service activities is in the form of training in making moringa latte. Before and after the training, a pretest and posttest were carried out to determine the level of knowledge of the service participants regarding making moringa latte. The target of this activity is the PKK Team of Ngargosari Village, Kulon Progo, Yogyakarta. The activity was carried out in September 2024. The Community Service Program in the form of training in making moringa latte at the PKK Team of Ngargosari Village went smoothly and the participants participated enthusiastically. The results of the pretest and posttest showed that the moringa latte training provided a significant and effective influence in increasing the level of knowledge and skills in making moringa latte.